Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1016/j.enpol.2011.09.028
|View full text |Cite
|
Sign up to set email alerts
|

Assessing energy supply security: Outage costs in private households

Abstract: The objective of this paper is to contribute to the topic of energy supply security by proposing a Monte Carlo-based and a survey-based model to analyze the costs of power interruptions. Outage cost estimations are particularly important when deciding on investments to improve supply security (e.g. additional transmission lines) in order to compare costs to benefits. But also, other policy decisions on measures that have direct or indirect consequences for the supply security (e.g. a phasing out of nuclear ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(29 citation statements)
references
References 12 publications
(3 reference statements)
1
23
0
3
Order By: Relevance
“…First, the consideration and weighting of the technical factors from Table 1 play a major role. If different assumptions are made in structuring the framework of the scenario, for instance about the duration or the regional location of the blackout [in the present case, Praktiknjo et al (2011) and Röpke (2013) consider Germany as a whole, Growitsch et al (2013) consider the level of the federal states, and Piaszeck et al (2013) consider the regional districts], then this affects the results obtained. Second, the subdivision of the industrial sectors influences the resulting VoLL values.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…First, the consideration and weighting of the technical factors from Table 1 play a major role. If different assumptions are made in structuring the framework of the scenario, for instance about the duration or the regional location of the blackout [in the present case, Praktiknjo et al (2011) and Röpke (2013) consider Germany as a whole, Growitsch et al (2013) consider the level of the federal states, and Piaszeck et al (2013) consider the regional districts], then this affects the results obtained. Second, the subdivision of the industrial sectors influences the resulting VoLL values.…”
mentioning
confidence: 98%
“…Upon closer consideration, it becomes apparent that, for example, the studies by Praktiknjo et al (2011), Growitsch et al (2013), Piaszeck et al (2013), and Röpke (2013) regard the whole of Germany as the area of study, but the damage costs differ greatly. Another explanation can, therefore, be found in the differences in the more detailed methodological structure of the studies.…”
mentioning
confidence: 99%
“…Praktiknjo et al . () conclude that such a decrease in the level of service reliability in Germany would cause significant economic costs.…”
Section: Previous Researchmentioning
confidence: 95%
“…In a case study approach focusing on the power interruptions that occurred in the US on 14-15 August 2003, Lacommare and Eto [13] estimated the cost to electricity consumers, indicating that the annual cost for power interruptions to US electricity consumers was around 79 billion USD. In Germany, Praktiknjo, Hahnel, and Erdmann [14] proposed a survey-based model to analyze the costs of power interruptions; Praktiknjo [15] used online survey data within a two-staged bottom-up regression model and implied that power interruptions are in average relatively expensive for residential consumers. The author also showed that the duration of a power interruption has a significant impact on the magnitude of the interruption costs.…”
Section: Related Literature Reviewmentioning
confidence: 99%